PENGARUH KEPEMILIKAN INSTITUSIONAL, KEPEMILIKAN MANAJERIAL DAN INTENSITAS MODAL TERHADAP KONSERVATISME AKUNTANSI (Studi Empiris pada Perusahaan Properties & Real Estate yang Terdaftar di Bursa Efek Indonesia Tahun 2017 – 2022) - Setiawan, Destia Dwisakinah; Hunein, Hamida (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
This study aims to provide empirical evidence of the influence of Institutional Ownership, Managerial Ownership, and Capital Intensity on Accounting Conservatism. This research uses a quantitative approach and the data used is secondary data. The population in this research is properties & real estate companies listed on the Indonesia Stock Exchange for the 2017-2022 period. The method for determining the sample uses purposive sampling. A sample of 7 companies was obtained over a 6 year period. The data analysis technique used is multiple linear regression analysis. The results of the F test show that simultaneously Institutional Ownership, Managerial Ownership and Capital Intensity have a significant effect on Accounting Conservatism. The results of the t test show that Managerial Ownership partially has no effect on Accounting Conservatism, but Institutional Ownership partially has a significant negative effect and Capital Intensity partially has a significant positive effect on Accounting Conservatism.